DEIKSIS SOSIAL DALAM NOVEL NEGERI 5 MENARA KARYA A. FUADI: Suatu Tinjauan Pragmatik - Rahmi Sari S; Syahrul R Syahrul R; Bakhtaruddin Nasution (Jurnal Bahasa dan Sastra, 2012)
The purpose of this study were to describe form, function and meaning of social deixis the novel Negeri 5 Menara works of A. Fuadi. The data of this research study is a word, phrases, and sentences in which there is use of social deixis the novel Negeri 5 Menara work of A. Fuadi. The findings on the use of social deixis are 82 kinds of novel forms of social deiksis words, 6 usage function deiksis dexsis socialist and social significance of the novel Negeri 5 Menara.